2014
DOI: 10.1007/s00404-014-3585-x
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy in women with abnormal uterine bleeding: a meta-analysis on four major endometrial pathologies

Abstract: Diagnostic accuracy for hysteroscopy is high for endometrial cancer, polyps and submucous myomas, but only moderate for endometrial hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 39 publications
1
36
1
4
Order By: Relevance
“…Hysteroscopy performed even better, when evaluated as a diagnostic tool for endometrial cancer, in terms of specificity. Despite a previous report demonstrating that hysteroscopy performs better in diagnosing rather than excluding endometrial cancer [22] in women with AUB, Gkrozou et al showed rather the contrary [4]. In their analysis, hys-teroscopy is more efficient in excluding rather than diagnosing endometrial cancer cases.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Hysteroscopy performed even better, when evaluated as a diagnostic tool for endometrial cancer, in terms of specificity. Despite a previous report demonstrating that hysteroscopy performs better in diagnosing rather than excluding endometrial cancer [22] in women with AUB, Gkrozou et al showed rather the contrary [4]. In their analysis, hys-teroscopy is more efficient in excluding rather than diagnosing endometrial cancer cases.…”
Section: Discussioncontrasting
confidence: 45%
“…In the meta-analysis from Gkrozou et al, hysteroscopy was found to have higher specificity than sensitivity when diagnosing endometrial cancer [4]. The 95 % CI was also wider for sensitivity than specificity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent meta- Neutral or somewhat disagree 4 11 analysis to determine the accuracy of hysteroscopy in diagnosing endometrial cancer, hyperplasia, polyps and submucous myomas, concluded that diagnostic accuracy for hysteroscopy is high for endometrial cancer, polyps and submucous myomas, but only moderate for endometrial hyperplasia [15].…”
Section: Discussionmentioning
confidence: 97%